1999
DOI: 10.1007/bf03217963
|View full text |Cite
|
Sign up to set email alerts
|

Chest size matching in single and double lung transplantation

Abstract: We applied predicted vital capacity to chest size matching between donor and recipient in lung transplantation to 15 single-lung transplant recipients with pulmonary fibrosis and to 20 double-lung transplant recipients with emphysema or non-emphysema. The predicted vital capacity of the donor was significantly correlated with the predicted vital capacity of the recipient both in double-lung transplantation (r = 0.79, p = 0.001) and single-lung transplantation (r = 0.71, p = 0.003). In double-lung transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…7 Our findings confirm this report, because, in standard lung transplantation, recipient size is a significant predictor of post-operative TLC as percent predicted; however, this correlation is not apparent in reduced-size lung transplants. Two reports, one dealing solely with single-lung transplantation 8 and another dealing with both single-and double-lung transplantations, 9 concluded that post-operative lung function is dependent on pre-operative recipient values and no donor-derived value can determine functional outcome. In contrast, a recent study dealing with living donor lung transplantation reported that post-operative forced vital capacity (FVC) is determined by the amount of donor lung tissue implanted and is not dependent on recipient factors.…”
Section: Discussionmentioning
confidence: 98%
“…7 Our findings confirm this report, because, in standard lung transplantation, recipient size is a significant predictor of post-operative TLC as percent predicted; however, this correlation is not apparent in reduced-size lung transplants. Two reports, one dealing solely with single-lung transplantation 8 and another dealing with both single-and double-lung transplantations, 9 concluded that post-operative lung function is dependent on pre-operative recipient values and no donor-derived value can determine functional outcome. In contrast, a recent study dealing with living donor lung transplantation reported that post-operative forced vital capacity (FVC) is determined by the amount of donor lung tissue implanted and is not dependent on recipient factors.…”
Section: Discussionmentioning
confidence: 98%
“…To avoid functional impairment, the amount of resected lung tissue has to be taken into account when size-reduced lung transplantation is performed [16]. Different opinions exist in the published literature as to whether postoperative lung function can be determined by donor or recipient factors [5,[17][18][19]. It has been shown that postoperative recipient TLC in size-reduced lung transplantation could be predicted by donor TLC with an excellent correlation between TLC and FEV 1 [5].…”
Section: Discussionmentioning
confidence: 99%
“…Significant discrepancies in between the volumes of the lobar graft and the respective hemithorax of the recipient can increase complications (4–6). Very large grafts can impair the function of the diaphragm as occurs in severe emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…In LDLLT, the lower lobe removed from the living donor is used as a graft to replace the whole lung of the recipient. Great discrepancy between the volume of the implanted lobe and of the thoracic cage of the recipient can occur and must be avoided, as it increases the risk of complications (2–8).…”
mentioning
confidence: 99%